Pengaruh CEO Narcisissm, Research and Development Investment terhadap Corporate Social Responsibility di Jakarta Islamic Index 70 dengan Ukuran Perusahaan sebagai Pemoderasi - Reza Oktavianti, Rista; Imanda Firmantyas Putri Pertiwi (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Corporate social responsibility pays attention to researchers and predecessors. The increasingly widespread industrial activities are paying more attention to corporate social responsibility (CSR). The existence of industry in Indonesia causes demands on companies to become higher and every company is required not to prioritize profits, but companies must also have concern for the environment and the prosperity of the communities around the industry. Factors that can influence corporate social responsibility (CSR) are CEO Narcissism, Research and Development Investment and Company Size. Design/methodology/approach: This research used secondary data in the form of financial reports and company annual reports and collected 28 samples from 124 populations. Research Findings: This paper shows that CEO Narcissism has an influence on CSR, R&D Investment has no influence on CSR, Company Size has an influence on CSR, Company Size can moderate CEO Narcissism on CSR, but Company Size cannot moderate R&D Investment on CSR. Theoretical Contribution/Originality: The researcher concluded the data that CEO Narcisssim can have an influence on the company's broad social responsibility (CSR) decision, R&D Investment cannot have an influence on CSR with investment not being able to make the company cover CSR broadly, Company Size can have an influence on CSR by The presence of high assets in a company can reveal CSR. Researchers also added company size as a moderator. The results obtained using data show that company size can moderate CEO Narcissism towards CSR but cannot moderate R&D Investment towards CSR.